Dampak Hubungan Kompetensi Penyuluh Peternakan dengan Keterampilan Teknis Peternak Ayam Pedaging - Mohamad Ikbal Bahua (AGRIMOR, 2022)
The success of the extension agent is determined by his competence in providing the information needed by the main actors and business actors in the fields of agriculture, fishery, and animal husbandry. This study aims to analyze the impact of livestock instructor competency factors related to the technical skills of broiler breeders. The research was conducted using the ex post facto method and was carried out in Gorontalo Province from May to August 2022. The number of respondents was 60 livestock extension workers and 60 native chicken breeders who were selected by purposive sampling. The results of the study indicate that the impact of livestock instructor competency factors related to the technical skills of broiler breeders are; leadership skills, the ability to plan extension programs, the ability to appreciate cultural diversity, the ability to organize counseling, the ability to utilize local resources, the ability to take social action, the ability to perform interpersonal relationships, and the ability to manage extension information.